Optimizing athlete safety: advanced strategies for preventing exertional heat stroke in collegiate football through strength and conditioning interventions - Judge, L. W.; Moore, M.; Bellar, D. (The Journal of Strength and Conditioning Research, 2025)
Ensuring the safety of National Collegiate Athletic Association football players is paramount, particularly because these athletes contend with the rigorous physical demands and high-impact collisions inherent to the sport. In recent years, the increasing body mass of collegiate football linemen has significantly heightened their risk for exertional heat stroke (EHS), a potentially fatal condition. This article critically examines the correlation between the larger body sizes of these athletes and the increased incidence of EHS. Although the health risks associated with oversized athletes are well-recognized, the practical challenges of addressing these risks remain complex. This article emphasizes the critical role of strength and conditioning (S&C) coaches in bridging the gap between awareness and actionable solutions. By exploring evidence-based strategies, including enhanced training protocols, heat acclimatization practices, comprehensive health screenings, wearable technology, and tailored emergency response plans, this article offers a rigorous, science-driven approach to creating safer athletic environments. Ultimately, the article aimed to advance the well-being of collegiate football linemen by equipping S&C coaches with the tools and knowledge necessary to effectively manage the unique challenges posed by the physical demands of their athletes.